‘I can’t pray’ – The spiritual needs of Malaysian Muslim patients suffering from depression - Md Rosli, Ahmad Nabil; Mohamed Saini, Suriati; N, Nasrin; Bahari, Rafidah; Sharip, Shalisah (International Islamic University Malaysia, 2015)

(untitled)
The mainstay of treatment of depression relies on pharmacological and psychological treatments. On top of that, evidence also recognizes the vital role of spirituality for human wellness which leads to growing interest in its utilization to treat depression. However, research on spirituality among Muslims in relation to depression is relatively scarce.